Low apolipoprotein A1 and high apolipoprotein B levels indicate specific lipid changes in treatment naïve early psoriatic arthritis - Kurt de Vlam; Rik Lories; M Van Mechelen; Sofia Pazmino; P Verschueren; Barbara Neerinckx; Lies Storms; Alla Ishchenko (RMD Open)
Objectives To investigate serum lipid profile in early, treatment-naïve psoriatic arthritis (PsA) and to determine whether changes in classical lipids or apolipoproteins are specific to PsA.Methods Total cholesterol, non-high-density lipoprotein cholesterol (non-HDL-c), low-density lipoprotein cholesterol (LDL-c), HDL-c, triglycerides, apolipoprotein B (ApoB) and apolipoprotein A1 (ApoA1) were compared in newly diagnosed untreated PsA patients (n=75) to sex- and age-matched controls (healthy control (HC)) (n=61) and early untreated rheumatoid arthritis (RA) patients (n=50).Results Among classical lipid measurements, HDL-c levels were lower in PsA than in HC and RA (df 2, χ210, p=0.006, PsA vs HC p=0.013). Significant differences in ApoA1 and ApoB levels were observed between PsA, RA and controls. ApoB was higher in PsA than in RA patients but lower than in controls (df2, χ243.8; p<0.001). ApoA1 was markedly lower in PsA patients compared with both RA and controls (df2, χ2118.9; p<0.001). In regression models, the levels of ApoA1, adjusted for additional factors, were predictive of PsA diagnosis with 90.6% accuracy. In receiver operating characteristic analysis, ApoA1 was predictive of the diagnosis of PsA with a specificity of 82.4% and a sensitivity of 83.8% at an optimal cut-off value of 1403 µg/mL (area under the curve (95% CI), 0.886 (0.83 to 0.941)).Conclusion Early, treatment-naïve PsA patients exhibit a distinct pro-atherogenic lipid profile, characterised by decreased ApoA1 and increased ApoB levels, distinguishing them from early RA patients and healthy controls. These findings highlight the potential of apolipoprotein measurements to serve as more accurate indicators of lipid disturbances in PsA than traditional serum lipids and as aid to diagnosis of patients presenting with early arthritis.